Functional Requirements for a HIS-RIS-PACS-Interface Design, Including Integration of “Old” Modalities - Adelhard, K.; Nissen-Meyer, S.; Pistitsch, C.; Fink, U.; Reiser, M. (Methods of Information in Medicine, 1999)
Radiology, Information Systems (RIS) and Picture Archiving Systems (PACS), have the potential for immense rationalization of operations in radiology and hence for the improvement of health care, as well as the return of investments. These systems must, however, be carefully designed such that they support routine work rather than being an additional burden to radiology staff. Analyses show that comprehensive communication of patient demographic and clinical data between RIS, PACS and Hospital Information Systems (HIS) are necessary prerequisites to achieve cost effectiveness. Based on analyses of radiology operations in a large university primary care hospital, functional requirements and data structures for designing HIS/RIS/PACS interfaces are presented. These concern communication of past examinations, associated written reports and images, appointment scheduling, requests of new examinations, digitizing old analog X-ray films, access from RIS/PACS to other clinical data, and transfer of new radiology reports and relevant images. Consistency of all redundant data stored in the three systems is essential. A pragmatic, safe and inexpensive method of electronically integrating “old” modalities not fully ”PACS capable“ in the HIS/RIS/PACS world is presented.
Keywords: RIS; PACS; Hospital Information Systems; Imaging; Communication; Interfacing